Indonesia's poverty puzzle: Chronic vs. transient poverty dynamics - Lilik Sugiharti; Miguel Angel Esquivias Padilla; Mohd Shahidan Shaari; Ari Dwi Jayanti; Abdul Rahim Bin Ridzuan (Cogent Economics & Finance, 2023)
Indonesia has lowered the total poverty rate by less than 10%. Earlier poverty measurements in Indonesia suggest that transient poverty is more prevalent. We argue that, when employing the Equally Distributed Equivalent (EDE) approach and disaggregated poverty lines, chronic poverty is more prevalent than transient poverty. We estimated chronic and transient poverty in Indonesia from 2007 to 2014 by employing a large longitudinal dataset and disaggregated poverty line measures at the district level. The empirical results are robust in various groups based on education, gender, marital status, location (urban-rural), and employment characteristics (status, farming and non-farming, type, and sector). The results indicate that chronic poverty accounts for at least two-thirds of total poverty. Poverty gaps based on education, regional location, gender, and employment are significant. Moreover, we assess whether poverty is linked to socioeconomic aspects and policy programs using quantile regression. The findings indicate that gender (female), age, number of household members, and household location are positively related to higher poverty and chronic poverty. Household head deaths and physical disabilities are positively associated with poverty. Although the urban-rural poverty gap has decreased, casual workers remain prone to poverty. Moreover, poverty is negatively linked to educational attainment, access to financial, transportation, and communication services, suggesting that improving these aspects may help reduce poverty. Social aid programs that support health, food assistance, education, and conditional cash transfers are negatively linked to both total and chronic poverty. Energy subsidies were not associated with lower levels of poverty.
Keywords: I32; O53; 330; Chronic poverty; educational access; gender gap; health system access; poverty alleviation; social assistance; social welfare programs; transient poverty